1973
DOI: 10.7326/0003-4819-79-4-500
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Abnormalities in Renal Failure

Abstract: Salt Lake City, UtahFifty-three patients with renal failure on chronic hemodialysis were screened for the presence of goiter. Thirty-one had enlarged thyroid glands, a prevalence of goiter of 58% not previously reported. Thyroid function studies showed low 131 l uptakes, low serum thyroxine and normal serum triiodothyronine and thyrotrophic hormone levels. Serum concentrations of thyroxine-binding globulin were normal; serum albumin concentration was only slightly reduced. Administration of synthetic thyrotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
3

Year Published

1975
1975
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 21 publications
0
21
1
3
Order By: Relevance
“…In the patients studied by Kaptein et al [13] in 1988, the prevalence of goiter was as high as 43% compared to only 6.7% in the control group. In another report, the prevalence of goiter in ESRD was 58% [14]. Lo et al [10] had correlated hypothyroidism with different levels of estimated GFR according to National Kidney Foundation CKD staging and concluded that reduced kidney function was associated with an increase in the prevalence of SCH and overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients studied by Kaptein et al [13] in 1988, the prevalence of goiter was as high as 43% compared to only 6.7% in the control group. In another report, the prevalence of goiter in ESRD was 58% [14]. Lo et al [10] had correlated hypothyroidism with different levels of estimated GFR according to National Kidney Foundation CKD staging and concluded that reduced kidney function was associated with an increase in the prevalence of SCH and overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some patients may have phys ical signs associated with thyroid disease: R amirez et al [113] observed a 58% incidence o f goiter in chronic hemodialysis patients which they attributed to an unknown goitrogenic substance, and Lim et al [88] found an enlarged thyroid in 30% of their dialyzed patients. In an isolated report, exophthalmos was frequently observed in chronic dialysis patients who were otherwise clinically euthyroid [123].…”
Section: Chronic Renal Failurementioning
confidence: 99%
“…PII levels vary considerably in patients on chronic hemodialysis [126], and peritoneal dialysis appears to substitute adequately for the renal excretion of iodide in nephrectomized patients [103], Iodine can also be eliminated by extrarenal routes, anephric individuals being able to excrete increased amounts of iodide in feces, saliva and sweat [103] [113,126] total T4 and FTI levels were reported. Furthermore, T3 was normal in one study [113] but low in two others [88,126], Thyroid hormone concentrations may decrease progressively with longer periods of hemodialysis [126]. Although it appears that total circulating hormone levels are not acutely affected during hemodialysis [37.…”
Section: Chronic Renal Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic renal failure have low serum levels of total triiodothyronine (TT3)1 due, in part, to a defect in the peripheral conversion of thyroxine (T4) to triiodothyronine (T3) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, the physiologic significance of the low serum T3 concentration in a variety of conditions (4)(5)(6), including uremia, has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%